The ACDSi 2014 - a decennial study on adolescents' somatic, motor, psychosocial development and healthy lifestyle - Bučar Pajek, Maja (Anthropological notebooks, 2015)
The Analysis of Children's Development in Slovenia (ACDSi) is a decennial study on children's and adolescents' somatic, motor, psychological and social development in Slovenia. In 2014, the study included 1,479 adolescents and young adults between 14 and 24 years of age. From its beginnings in 1970, it has been characterised as an interdisciplinary study of physical anthropology, kinesiology, psychology and sociology. In its third cycle on adolescents in 2014, the study was expanded to include public health issues. The aim of the study is to observe the secular trends of the somatic and motor development of adolescents in Slovenia regarding the psychological, social and health determinants that shape contemporary adolescents' lifestyles. This paper describes the protocol of the ACDSi 2014 study with regards to its organisation, sampling and methods.
Keywords: mladostniki; telesni razvoj; gibalni razvoj; telesni fitnes; zdravje